PERAN WANITA TANI DALAM PENGAMBILAN KEPUTUSAN USAHATANI - Shenny Oktoriana; Anita Suharyani (Universitas Sebelas Maret, 2021)
Male farmers are considered as the main subject in managing a farm. This condition has an impact on almost of farmer capacity-building programs involving only male farmers. In fact, the role of women farmers in managing their farming is inseparable. Therefore, the study aims to measure the level of the role of women farmers in decision-making in farming activities. The research was conducted in Limbung Village of Kubu Raya District, which involved 64 respondents. Data were collected through interviews with respondents and were analyzed descriptively. The result of the research showed that women farmers who had a higher level of activeness in the women farmers group tend to have more influence in the decision making in their farming activity, compared to the women farmers with a lower level of activeness, although the final decisions still made by men. Therefore women farmers' involvement in farmers' capacity-building programs is an essential matter for agricultural development.